The Dominant Factor in Educational Digitalization Sustainability: Structural Equation Modeling of Technology Acceptance Versus Digital Literacy on Student Learning Outcomes - Nur Indah Septia Ningsih; Haryadi; Bernadus Wahyudi Joko Santoso (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines the dominant factors influencing student learning outcomes in digital mathematics learning, focusing on Technology Acceptance and Digital Literacy. A unified model combining the Technology Acceptance Model (TAM) and Digital Literacy framework was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The participants were 125 fifth-grade students from three public elementary schools in Cirebon. Data were collected through validated questionnaires measuring Perceived Ease of Use, Perceived Usefulness, Attitude, Digital Literacy, and mathematics learning outcomes. The findings showed that all hypothesized relationships were significant (p < 0.001). Digital Literacy had a stronger effect on learning outcomes (β = 0.415) than Technology Acceptance (β = 0.311), with the cognitive dimension contributing the most (β = 0.521). The results also indicated that Digital Literacy fully mediates its dimensions, while Technology Acceptance influences learning outcomes through sequential pathways involving perceived usefulness and attitude. The study concludes that Digital Literacy is the main predictor of learning outcomes in digital mathematics learning. Therefore, sustainable educational digitalization should prioritize strengthening students’ digital literacy competencies alongside technology adoption.